2010
DOI: 10.1259/dmfr/91657756
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the diagnostic accuracy ofin vivoandin vitrophotostimulable phosphor digital images in the detection of occlusal caries lesions

Abstract: Objectives: The purpose of this study was to compare the accuracy of diagnoses of occlusal caries lesions from digital images captured using a photostimulable phosphor (PSP) sensor under in vivo and in vitro conditions and to present useful clinical data regarding the clinical application of the system. Methods: The study sample comprised 60 mandibular third molars (30 sound and 30 with occlusal caries) requiring extraction. A pre-extraction and post-extraction image of each tooth were acquired using a PSP sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…These modalities also make it possible to measure caries depth, which can be useful in the diagnosis, treatment planning, management, and follow-up of dental caries. However, because intra-oral systems can only provide two-dimensional information about dental tissue and disease, their ability to measure caries depth is affected by beam angulation, imaging settings, and patient-related factors [10][11][12][13][14][15]. Cone-beam computerized tomography (CBCT) was introduced in response to the high demand for a technique that could provide three-dimensional data at the tooth level.…”
Section: Introductionmentioning
confidence: 99%
“…These modalities also make it possible to measure caries depth, which can be useful in the diagnosis, treatment planning, management, and follow-up of dental caries. However, because intra-oral systems can only provide two-dimensional information about dental tissue and disease, their ability to measure caries depth is affected by beam angulation, imaging settings, and patient-related factors [10][11][12][13][14][15]. Cone-beam computerized tomography (CBCT) was introduced in response to the high demand for a technique that could provide three-dimensional data at the tooth level.…”
Section: Introductionmentioning
confidence: 99%
“…There also is disagreement in the borderline cases in the method of doing the radiographic diagnosis of the disease [29]. However, past research showed that software enhancement tools that adjust contrast, density, image size, etc., do contribute to the closeness in diagnoses among observers [32].…”
Section: Introductionmentioning
confidence: 88%
“…The fuzziness of X-ray film also produces doubt for diagnosis of boundary line at the apical lesion [31]. Aside from the mentioned drawback, another factor that affects the evaluation of periapical disease is the variation in dentists' assessments [29] [32][33]. For example, research by Lanning [34] had reported that there is significant variability in periodontal diagnosis and treatment planning among dental schools [34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in vivo time efficiency was found to be very good for single radiographs of mandibular third molars. 17 Under in vitro conditions; the diagnostic ability of visual inspection, conventional film, charge-coupled device (CCD) sensor, and PSP sensor were found similar in the diagnosis of proximal lesions in posterior teeth when compared with the histological gold-standard. 4 In order to obtain optimum image quality, an intraoral radiographic examination should be used with aiming equipment.…”
Section: Dentomaxillofac Radiol 48 20180250mentioning
confidence: 96%